Digital Labour Platforms and Trade Unions - Convergences and divergences in the use of Facebook by a traditional union and a new virtual union - Marques Alves, P. (XX Congresso Mundial de Sociologia, 2023)
In the context of the "flexible accumulation” (Harvey, 1989), that strongly reinforces the destructive nature of capital (Mészáros, 1996), digital labour platforms have emerged and quickly became widespread. They raise new questions regarding social labour relations, and outline “challenges and opportunities for trade unions” (Pötzsch and Schamberger, 2022) and for collective action. Although, forms of individual and collective resistance using several repertories (Tilly, 2006) have emerged, what was considered almost impossible a short time ago, as we are face to “nonstandard workers”, that are “hard-to-organise” (Molina and Guardiancich, 2018). However, traditional unions are trying to organise them, alongside with new forms of unions, namely virtual unions, some of which only exists in social media, or other kind of associations, both nationally and internationally. In Portugal there are a virtual union with presence on Facebook, the social media that is largely dominant in the country: Drivers’ Union TVDE Portugal. This presence is accompanied by the presence of traditional unions, such as STRUP, affiliated to the class oriented CGTP-IN, a union that had recently held the election of two union representatives among these workers. The aim of this paper is to analyse how these unions are using Facebook. Are the virtual union using it to communicate with the workers in the same way as the traditional union or not? Is Facebook used by them to mobilise the workers? Are the levels of interaction high or low? For answering these questions, we have examined the online content of these two unions across 2022. Our main conclusion is that the way Facebook is being used does not give a contribution to the mobilisation of these workers, mainly in the case of the virtual union, since its posts are almost all purely informative. In both cases, the levels of interaction are very limited.